Financial sector and output dynamics in the euro area countries - Marcus Kappler; Frauke Schleer; Willi Semmler; Timo Teräsvirta; Peter Winker (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
The financial and economic crisis has drawn attention to the need for a better understanding of destabilising effects that arise in the financial sector and spill over to the real economy. In turn, weakening economic conditions are likely to feed back to the financial sector, thus giving rise to an adverse feedback loop. The results of past studies indicate that financial stress - which is a reflection of vulnerability in the financial system - has a strong regime-specific impact on the real economy. Thereby, the literature distinguishes between high and low financial stress regimes. Almost all past studies have found that the financial sector exerts extremely negative effects after an increase of financial stress on economic activity in a distressed period and relatively small or even negligible negative effects in a low stress period. What has been lacking so far is research on financial sector and output dynamics as they may unfold over time. During some downswings the effect of financial sector instability on economic activity may be more severe than during others. – – Die Finanz- und Wirtschaftskrise hat die Notwendigkeit für ein besseres Verständnis von destabilisierenden Effekten des Finanzsektors und deren Auswirkung auf die reale Ökonomie verdeutlicht. Umgekehrt kann aber auch die schlechte Wirtschaftslage wiederum Druck auf den Finanzsektor ausüben, was zu weiteren negativen Feedbackeffekten führen kann. Vor diesem Hintergrund beschäftigt sich eine Studie im Rahmen des ZEW-Forschungsprogramms SEEK mit der Rolle destabilisierender Effekte, die aus dem Finanzsektor entstehen. Die Studie zeigt, dass sich Finanzmarktstress nicht immer negativ auf den Output auswirkt.
Keywords: 330